Efficacy and tolerability of psychostimulants for symptoms of attention-deficit hyperactivity disorder in preschool children: A systematic review and meta-analysis. Issue 1 (15th February 2023) - Chiu, Hsien-Jane; Sun, Cheuk-Kwan; Cheng, Yu-Shian; Wang, Ming Yu; Tzang, Ruu-Fen; Lin, Feng-Li; Cheng, Ying-Chih; Chung, Weilun
Abstract: Background: There was no previous meta-analysis investigating the efficacy/tolerability of psychostimulants for symptoms of attention-deficit hyperactivity disorder (ADHD) in preschool children. Methods: Databases including PubMed, the Cochrane Library, EMBASE, ScienceDirect, and ClinicalTrials.gov were searched from inception to March 2022 for randomized controlled trials (RCTs) on therapeutic efficacy of psychostimulants against ADHD symptoms in preschool children (age ≤6 years) compared with placebos. Primary outcomes were (a) changes in ADHD symptoms evaluated by validated rating scales from parents'/teacher's observation, or (b) post-intervention improvements in neuropsychological performance. Secondary outcomes were risks of adverse events. Results: Meta-analysis of nine eligible trials including 544 preschool children (mean age=4.86 years, female=11.98%, median treatment duration=4.33 weeks) supported the efficacy of psychostimulants against global symptoms from observations of parents (Hedges' g=0.6152, p<0.0001) and teachers (Hedges' g=0.6563, p=0.0039). Efficacy of psychostimulants was also noted against symptoms of inattention and hyperactivity/impulsivity, especially the latter (i.e., main symptoms in preschool children). Moreover, male gender, older age, and longer treatment duration were associated with better efficacy. Regarding adverse events, only the risk of poor appetite was higher in the psychostimulant group (odds ratio [OR]=2.39). However, the qualities of evidence were low to very low, indicating potential discrepancy between the true and estimated effect. Conclusions: Our results showed that psychostimulants might be beneficial for preschool children with ADHD, especially hyperactivity/impulsivity from teachers' observation, with tolerable side effects. Nevertheless, the true magnitude of the effect needs to be confirmed with more research due to low to very low certainty of the evidence.